TINGKAT KESUKAAN KONSUMEN TERHADAP TEPUNG DARI BEBERAPA JENIS PISANG DENGAN LAMA PENYIMPANAN BERBEDA - Rusmini Rusmini; Ali Sadikin (Politeknik Pertanian Negeri Samarinda, 2017)
Bananas including fruits are perishable, one way to enhance the value to bananas by processing into flour. The layout of the plantations that far with the treatment site causes bananas harvested storage should experience some time before it is processed into flour, but still can be processed into flour with good quality. This study aims to understand the interaction between the types of bananas with storage time, and to determine the type and duration of storage of bananas which have characteristics that best banana flour. This research was conducted at the Laboratory of Plant Physiology, Laboratory of Agricultural Product Processing and Basic Laboratory University Mangkurat Banjarbaru for 4 months. The design environment used in this study is a randomized block design (RAK) while the design of the treatment is the draft Petak Separated (Split-Plot Design) where the main plot is a type of banana (A), which consists of 3 levels, while the subplot is the storage time (B) consisting of 6 level. Bananas (A), which consists of three levels, namely: a1 = Banana Kepok / Descending, a2 = Bananas Cotton and a3 = Banana Awa and retention (B) consisting of six levels ie: b0 = Not saved (0 days), b1 = Saved (1 day), b2 = Saved (2 days), b3 = Saved (3 days), b4 = Saved (4 days) and b5 = Saved (5 days) were tested with non-parametric statistical Kruskal hedonic method -Wallis , The results showed that the organoleptic test by using the Kruskal-Wallis analysis of the level of consumer preferences in color, texture and smell indicates that no significant effect on the level of consumer preferences. This means, any kind of bananas gives the same effect on everyone's favorite will be the color, texture and smell of banana flour.